Development of SS 304L composite coatings on mild steel substrate using friction surfacing and wear characterization. (2022) - Rajoria, Vibhor; Nain, Gurpreet; Vijayan, S.; Prasad, C. Hariram; Damodaram, R.; Karthik, G.M.; MD, F. Khan
Abstract: Friction surfacing is a novel solid-state surfacing process used to improve the performance of an underlying metallic surface. This work aims to develop the stainless steel 304L coatings on mild steel substrate by employing friction surfacing to improve the wear resistance. SiC, TiB2 and tungsten reinforced particles were packed inside the stainless steel 304L rods and used as consumables. The microstructures of the composite matrix were characterized using optical and scanning electron microscopy. The hardness of the friction surfaced coating was evaluated using Vickers microhardness testing. Further, the sliding wear behaviour was studied and analysed using a pin-on-disc experiment. The wear resistance of the reinforced composite coating is significantly improved which may be attributed to the high hardness and reduction in the effective contact area.